Implementasi Metode Pembiasaan Untuk Penanaman Nilai-Nilai Akhlak Di Smp Muhammadiyah Plus Klaten Utara Tahun Ajaran 2016/ 2017 - Hasanah, Meirina Nur, Dr. Syamsul Hidayat, M.Ag (2017)
Morals are attributes embedded in the human soul that can give birth to a good or bad deed without doing any thinking and judgment. The purpose of moral coaching is the realization of an inner attitude that can encourage spontaneously to give birth to good deeds spontaneously. Implementation of moral values is an important thing to apply to learners by using many methods, one of which is the habituation method. Good habituation need to be applied to children from childhood, because by starting from childhood to make the child more easily accept and understand. The application of moral values with the method of habituation is intended so that children can apply morals to God, morals to the Prophet, morals to self, and morals to fellow human beings. The formulation of the problem in this research is how the process of implementing methods of habituation in implementing moral values in SMP Muhammadiyah Plus Klaten Utara, how the results of the implementation of moral values through the method of habituation in SMP Muhammadiyah Plus Klaten Utara. In this study, the object of research is the students of class VII and VIII SMP Muhammadiyah Plus Klaten Utara. Type of Field research, using a qualitative approach. Methods of data collection by observation, interview and documentation. The purpose of this study is to know the implementation of methods of habituation done SMP Muhammadiyah Plus Klaten Utara in the implementation of moral values, to know the results of the implementation of moral values through the method of habituation in SMP Muhammadiyah Plus Klaten Utara. From the results of this study can be concluded that the implementation of methods of habituation applied in some activities containing moral values such as habituation of discipline, tahfidz activities, habituation smile and greetings, dhuha prayer habits, hajj prayers, training young da'i. With the method of habituation will form Islamic behavior in children who are able to face challenges outside by having good character as a guide in accordance with the Islamic shari'ah.